Furies - Hall, Peter; Harrison, Tony; Aeschylus, Eumenides (The Oresteia trilogy / Aeschylus, 1983)
Having avenged his father's murder by killing his mother, Orestes now pursued by the Furies because he has commited matricide-takes refuge at the shrine of Apollo, who promises protection and sends him to seek justice from Athena. The ghost of Clytemnestra rouses the Chorus of Furies to bring her murderer to justice, Athena, goddess of wisdom, judges between Orestes, who murdered his mother tyo arrange his father, and the Furies, who demand revenge for the murder of Clyemnesta,. Her decision reflects the historical turning in Athena from personal retribution to community law.